THE INFLUENCE OF NON-PHYSICALY WORK ENVIRONTMENT AND JOB SATISFACTION ON WORK MOTIVATION PT CAHAYA SEJAHTERA LESTARI DRINKING WATER DISTRIBUTOR - Putri, Ratna Komala; Muttaqien, Ilman; Prabowo, Deni Haryo (CENTRAL ASIA AND THE CAUCASUS, 2022)
The main focus of the research is motivation employees work at PT Cahaya Sejahtera Lestari especially Drinking Water Distributor, Motivation is an impulse that makes employee to work so the purpose or satisfaction will be achieved.Companies should increase the motivation employees, because motivation an employee will impact on labor productivity employees.There are many factors that can affect motivation, work in this attractive operating environment researchers is non-physical and satisfaction work. The purpose of this study was to determine the description of a non physical work environment , job satisfaction and motivation work employees of PT Cahaya Sejahtera Lestari especially Drinking Water Distributor, and also know the effects of non-physical work environment on motivation , job satisfaction on motivation and the effects of non physical work environtment and job satisfaction on work motivation at PT Cahaya Sejahtera Lestari especially Drinking Water Distributor This research uses descriptive and verification methods with a population of 100 employees and a sample of 80 employees. The analysis technique used is Pearson product moment correlation coefficient and multiple regression analysis. Hypotesis tests are using the F-Test and t-Test. The results of this study can be concluded that both non- physicaly work environtment and job satisfaction have a positive and significant effect on work motivaion. Partially, non-physicaly work environtment a positive and significant effect on work motivation. And job satisfaction has a positive and significant effect on work motivation.